Incidence of Chronic Kidney Disease Related Pruritus and its Relation with Sleep Quality among Patients on Hemodialysis in Pakistan - Qurat Ul Ain, Muhammad Sheheryar Asghar, Mohiuddin Saleem, Sana Majeed, Rubab Rameez, Sidra Shaukat (Pakistan Journal of Medical & Health Sciences, 2022)
Due to injured kidneys, CKD is defined as a glomerular filtration rate of less than 60ml/min/1.73m2 for more than 3 months. The lethal stage of chronic CKDs is the last stage of renal disease, and its frequency has increased over the previous 30 years. Pruritus caused by chronic renal disease is an unpleasant illness that causes itching and reduces sleep quality. The goal of this study is to look at the characteristics of pruritus in people with CKD and how they relate with sleep quality among patients on maintenance hemodialysis. Place and Duration: In the department of Medicine & Nephrology of Lahore General Hospital and Islamic International Medical College Trust Railway General Hospital, Rawalpindi for six-months duration from April 2021 to September 2021. Methods: 60 chronic renal disease patients were gathered from the nephrology department. Inclusion criteria included all patients with CKD who had pruritus and had sleep disturbance, while exclusion criteria included all patients who had rashes and pruritus that were not caused by CKD and were caused by other disorders. Age, gender, sleep pattern, disease severity, poor sleep quality, & pruritus location were all investigated by all patients. Results: CKD-associated Pruritus was distributed as follows: 75 percent of all patients were 45 years old or older, whereas 25 percent were 45 years old or younger. Pruritus interfered with sleep in 41.7% of patients, but not in 58.3%, and 30.1 percent of patients were girls and 73.9 percent were men. About 55% of people with pruritus are severely affected, whereas 45% are not. The trunk accounts for 60% of pruritic patients, whereas the rest of the body accounts for 40%. There was a strong link between the degree of pruritus and gender, the afflicted region, and sleep. Conclusion: Pruritus, often known as "uremic pruritus," is the most common skin complaint in people with ESRD. Due to the lack of a clear relationship with uremia, a substantial association occurs in males over the age of 45, disrupts sleep, and predominates in the trunk area.